GEOMORPHOLOGICAL CHARACTERISTICS OF THE PASIRPANJANG AREA AND ITS SURROUNDINGS, CIRACAP, CILETUH, SUKABUMI DISTRICT, WEST JAVA PROVINCE - Fibrian, Achmad Viki; Pratiwi, Santi Dwi (Journal of Geological Sciences and Applied Geology, 2026)
The study site is considered in the Pasirpanjang and its environs area of Ciracap District, Sukabumi Regency, West Java which has a geomorphologic diversity that could be affected by endogenic and exogenic processes. Therefore, the objectives of this study are to determine the geomorphological features of the area by using morphographics, morphometrics and morphogenetic aspects. We analysis DEM, obtain field data and a review of literature is made. Morphographic analysis consists of landforms and river flow patterns, morphometric analysis includes slope gradients and morphogenetic anlayisis arranges lithology, geological structure and river flow patterns. Study result indicates truly cartographic aspects of the terrain are two types: low hills and high hills; subdendritic and rectangular patterns with changes in slopes ranging from gentle to steep. The geology in the region of the outer rim is caused by tectonic and volcanic activity, as well as exterior weathering and erosion still occurring. The study area is divided into three major geomorphological units depending on combination of these 3 geomorphologic attributes. The findings contribute to a significant geomorphological interpretation that can serve as an important reference for land use planning and mitigation of potential geomorphologic disasters, as well as the advancement of applied geological researches in the Ciracap area and its adjacent locations.